Ossifying Fibroma of Maxilla: A Diagnostic Engima - Singh, Priya; Malik, Upender; Manna, Arpan; Vaishali; Mahfooz, Aiman (International Journal Of Drug Research And Dental Science, 2022)
Fibro-osseous lesions are a diverse group of processes that are characterized by the replacement of normal bone with fibrous tissue containing a newly formed mineralized product. Ossifying fibroma is a rare entity among the other type of fibro-osseous lesions which is a slow-growing, well-circumscribed benign tumor of bone that probably arise from the cells of the periodontal ligament. In the present case, the report discusses an 18-year-old female patient who reported painless swelling in the upper left back tooth with misleading clinical features.